Dietary and biomarker estimates of fatty acids and risk of colorectal cancer. Issue 5 (27th February 2015) - Hodge, Allison M.; Williamson, Elizabeth J.; Bassett, Julie K.; MacInnis, Robert J.; Giles, Graham G.; English, Dallas R.
<x xml:space="preserve">Abstract</x> The associations between intake of or circulating fatty acids and risk of colorectal cancer (CRC) are unclear. We examined prospectively the associations between dietary or biomarker fatty acids and CRC. For 41, 514 men and women, aged 40–69 years, baseline (1990–94) dietary intakes of fatty acids were estimated using a food frequency questionnaire and plasma phospholipid (PPL) fatty acids were measured for 4, 205 participants including 395 CRC cases, according to a case‐cohort design. Hazard ratios were computed using Cox regression adjusting for education, alcohol intake, smoking status, physical activity and total energy intake; and stratified for gender, ethnicity and family history of cancer, with age as the time scale. We assessed the heterogeneity of associations with colon and rectal cancers. PPL saturated fatty acids (SFAs) were positively associated with CRC risk, while total n‐3 polyunsaturated fatty acids (PUFA) and long chain marine n‐3 PUFAs showed inverse associations, significant only for 22:5 n‐3. No significant associations were observed for dietary fatty acid intakes but positive associations with CRC of borderline significance were seen for both dietary and PPL linoleic acid. Positive associations with dietary palmitic acid (16:0), MUFAs and n‐6 PUFAs were seen for rectal but not colon cancers. PPL 22:6 n‐3 was inversely associated with rectal cancer. Limiting intakes of SFAs and MUFAs could be assisted by following existing guidelines to limit red and processed meats which are important sources in the Australian diet. Our observations regarding linoleic acid should be examined further.